Editorial Preface - Estadieu, G; Marcos, Aderito; Caires, Carlos; Mendes, Daniel; Rodrigues, Nuno (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)

An Integrated Learning Platform Focusing on STEAM and Collaborative Modules for Macau - Cheng, Un Man; Abreu, Filipa C. A. Martins de (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
In Macau, the effectiveness of traditional classroom learning is questioned as the problem is discovered by the changes in technology advances, social media, and the varieties of learning methods. Learning experiences, interests, discoveries, and creativity development are considered essential to ac...

An Integrated Learning Platform Focusing on STEAM and Collaborative Modules for Macau - Cheng, Un Man; Martins de Abreu, F. (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
In Macau, the effectiveness of traditional classroom learning is questioned as the problem is discovered by the changes in technology advances, social media, and the varieties of learning methods. Learning experiences, interests, discoveries, and creativity development are considered essential to ac...

Design Explorations for 3D-Printed Modular Markers for eXtended-Reality Tangible User Interfaces: - Iok Fong, Chau; Cardoso, Jorge C. S.; Estadieu, Gerald Vincent (International Journal of Creative Interfaces and Computer Graphics, 2022)
Various materials, objects, and sensors have been explored earlier for creating tangible user interfaces (TUIs). However, there is little work on 3D-printed TUIs based on visual markers for smartphone-based extended reality (XR) experiences. The combination of visual markers and smartphones results in cheap, accessible XR systems within reach of many people. Combined with 3D printing, it could foster do-it-yourself (DIY) projects for XR experiences, which may further expand and open-up possibilities for accessible and tangible interaction. This work explores the design space of modular 3D-printed tangibles for smartphone-based XR. The authors report the design exploration process, provide several interactive 3D-printed markers, and reflect on the resulting possibilities.

An Attempt to Examine Digital Native and Digital Immigrant Macau Graphic Designers' Perceptions of Adopting Generative Design - Lau, Ching Man; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
The manifestation of generating digital visuals through an algorithm is gaining worldwide attention in the graphic design industry. It is a new form of computing that visualizes data input by the designer or collected in the physical environment and turns them into artwork. The generative design of...

Multimodal Game Design Framework for Creativity in Macau's Educational System Through Digital and Tangible Games: Chinese, Portuguese, and English Languages - Martins de Abreu, F.; Barbosa, Álvaro Mendes (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
Creativity and collaboration are crucial to learning development in today's fast-paced educational environment. New technology can bridge humans and their natural needs through immersion in digital environments with physical objects. As knowledge and information evolve, digital interactive experienc...

In Memorial and Serenity: Introducing VR Grave Mourning in the Chapel of St. Michael in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics, 2022)
Macao inhabit a population of 683,100. The birth rate has been dropping while the death rate has risen compared to two years ago. Cemeteries are becoming crowded, and burial spots are demanding. In this case, video calls and social media can be the solution. How about our beloved ancestors? Can we video call them on their memorial days? This paper presents a VR experience of immersing oneself in the 3D VR of the Chapel of St. Michael of Macao to create a peaceful atmosphere for grave mourning. The chapel is also a personal space where we can be truly isolated in serenity. It is a retreat to pray, disconnect, and reconnect to the beloved deaths that may not be buried in an easily accessible location. The authors propose a possible future of mourning our loved ones through virtual reality and telepresence: an immersive experience connected with Macao's extraordinary and cultural unicity.

A touristic habitation: automobilities of Chinese driving tourists - Yang, Peng; Xu, Honggang; Hannam, Kevin (Tourism Geographies, 2022)
As an emergent tourism sector, driving tourism connects car use and touristic activities intimately. Following the notion of the ‘inhabited car’, this article explores how and why Chinese tourists inhabit a travelling car for drivers/passengers in the leisure automobility and driving tourism context. Through three different road trips and ‘mobile methods’, it was found that Chinese tourists inhabit the car in four ways: driving, gazing, listening, and communicating. Through this embodied habitation, the car is turned into a ‘touristic inhabitation’ space for protecting the tourists generating touristic emotions、social interactions, and tourism meanings. The study contributes to automobility and tourism literature and provides implications for driving tourism development in China.
Keywords: Automobilities; China; cars; driving tourism; habitation

La terre des autochtones potiguara du brésil: une construction sociale et politique - Simões, José Manuel (E-Journal of Intercultural Studies, 2022)
The land of the potiguara indians of Brazil: a social and political construction The space in which the potiguaras of Brazil live is, today as in the past, the result of a longterm process, many negotiations and well-managed refuges. Paradoxically, despite their recurrent discourse invoking the ancestry of their lands of origin, the Potiguara fight and continue to fight politically for the return to the spaces where their colonial refuge took place.

Temporary transnational labour mobility and gendered individualization in Europe - Harsløf, Ivan; Zuev, Dennis (Mobilities, 2022)
In a context of a new transnational division of labour, temporary international labour mobility is on the rise in Europe. In particular, recent decades have seen considerably more women seeking work experience abroad. Observers have been concerned with how such mobility is related to individualization, and in particular how it may challenge collective institutions, communities and families. The aim of this study is to explore such issues among women and men with international work experience. Using data from European Social Survey, the paper investigates previously mobile workers in terms of their current working and living conditions. Across genders, we consider different forms of individualization that may be associated with transnational labour mobility. While both women and men with transnational work experience generally feature strong strategic individualization, this is most pronounced among men. Hence, men's mobility is among other things associated with increased autonomy in working life, while – in contrast to women – it does not seem to hamper their integration in the sphere of social reproduction.
Keywords: Europe; Temporary labour mobility; individualization; sphere of production; sphere of social reproduction; transnational division of labour

Modulações em português de imagens, experiências e estesias orientais: revisão das razões do fascínio de alguma dicção poética chinesa e japonesa como utopia da poesia - Borges, Vera (Alea: Estudos Neolatinos, 2022)
Resumo O fascínio do Ocidente pela dicção poética oriental está atestado em várias latitudes e línguas, e resultou numa profícua produção na área da poesia. Sabe-se que a reinvenção da poesia chinesa da autoria de Pound, em grande medida na origem da sua proposta de revolução do idioma poético, nas primeiras décadas do séc. XX, assentou, na verdade, numa falácia; numa concepção errada da natureza da escrita chinesa (e japonesa) como essencialmente pictográfica e ideogramática, na base de propriedades expressivas reconhecidas na poesia que resultariam numa particular eficácia na apreensão e tradução do real. Pessanha enaltece, em termos similares aos da exaltação poundiana, a escrita da poesia chinesa clássica. Interessa-nos rever alguns inventários dos traços da dicção poética chinesa e japonesa que explicam que ela seja tomada como metonímia e metáfora da poesia, ou como meta e utopia da poesia, para perceber o que terá levado autores muito díspares a tentar a mão nos haikus, processo em que sondaremos algumas formulações poéticas em língua portuguesa. Consideramos também que esse fascínio por uma (sonhada) origem da dicção poética, quando cruzada com o habitar (não metafórico, neste caso) do pequenino enclave de Macau, de autores que nele lançaram raízes, resultou em alguns exercícios poéticos particularmente felizes e singulares. Serão trazidos à colação nesta abordagem poemas de Eugénio de Andrade, Sophia de Mello Breyner Andresen, José Tolentino Mendonça, Yao Feng, Fernanda Dias e Fernando Sales Lopes.
Keywords: Macau; Pound; falácia; haiku; poesia; poesia chinesa; trocar de voz

Diversity and Variation in China's Yao Ancient Wood Frame Structures Through Genetic Algorithms: - Afonso, Filipe; Jedenov, Kirill; Januário, Pedro Gomes; Almeida, Paulo (International Journal of Creative Interfaces and Computer Graphics, 2022)
This study, focusing on the China's Yao minority community, investigates the feasibility to create a generative computational method to replicate the diversity of the existing Yao traditional wood buildings, addressing the critical issues currently facing computational design methods, in the attempt to adapt genetic-generative algorithms to the study of local ancient architecture. The project develops a computational tool to generate a network of three-dimensional prototypes, or building structures, derived from traditional wood frame village houses. It studies possible housing structures that illustrate some of the key working methods available in digital systems such as ‘generating' and ‘compositing' taking as a starting point computational strategies oriented towards geometry and where a set of local variables play a decisive role: available local technologies, use of raw materials, and the dimensioning of timber components based on data collected from Yao architecture.

A Critical Look at Blockchain-Interactive Generative Art - Farinha, Daniel Filipe (International Journal of Creative Interfaces and Computer Graphics, 2022)
Artists are increasingly using blockchain as a tool for trading digital artwork as non-fungible tokens (NFTs); however, some are also beginning to experiment with the blockchain as a medium for generative art, using it as a seed for a generative process or to continuously modify an evolving piece. This paper surveys, reviews, and classifies the state-of-the-art in blockchain-interactive NFTs and presents a liberal-arts critique of the opportunities and threats posed by this technology, whilst addressing existing criticism on the broader topic of art-related NFTs. The paper examines some of the most experimental pieces minted on the Hic et Nunc (HEN) and Teia NFT marketplaces, for which a purpose-built research tool was developed. The survey reveals some reliance on centralised infrastructure, namely blockchain indexers, placing undesired trust on third parties which undermines the potential longevity of the artwork. The paper concludes with recommendations for artists and NFT platform designers for developing more resilient and economically sustainable architectures.
Keywords: Art Preservation; Blockchain; Crypto Art; Dynamic NFT; Generative Art; Non-Fungible Token; Provenance